Prospective Biology Teachers Perceptions of CT, ICT and TPACK Skills - M Haviz; Ika Metiza Maris; Ervina Nasrul (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
The Covid-19 pandemic has caused the learning process to change from face-to-face to online learning, without exception it has also occurred at Islamic Universities in Indonesia. Therefore, an online learning design with WhatsApp and Google Classroom was conduct to improved critical thinking (CT), information communication and technology (ICT), and technological pedagogical content knowledge (TPACK) of Prospective Biology Teachers in Islamic Universities (PBTs-IU). The aims of this study was to investigate prospective biology teacher’s perceptions of critical thinking, ICT and TPACK skills of during the Covid-19 pandemic. This study used quantitative descriptive method. Data were collected from 195 PBTs-IU, with of 19 males and 176 females. The quality of the instrument was achieved use confirmatory factor analysis (CFA) and alpha Cronbach tests. Then, paired sample correlations test was used to confirmed the hypothesis. The result of the study showed that there is different with CT, ICT and TPACK skill pre-course with post-course PBTs-IU. This finding also showed that score CT, ICT and TPACK of PBTs-IU for post-course is higher than pre-course. In concluded, there was a significant difference score for pre-course and post course about prospective biology teacher’s perceptions of CT, ICT and TPACK skills of during the Covid-19 pandemic.